(untitled) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2017)
Saka is a phenomenon that has long existed in the community of Southeast Asia and is often associated with the culture of the Malay community in Malaysia. The concept of saka associated with the relationship between humans and spirits or ghosts for a particular purpose. The objective of this study is to identify the existence of saka by utilizing scientific approach. This study is a pilot study which has utilized experimental methods and case study. Only one respondent participated in this study with the main features of possessing saka. Data is derived from the body’s response equipment (biofeedback) and aura body colour machine. The study has found that individual who has saka shows special colour (red) on ertain parts of their body. However, this study has not yet managed to establish a link between certain phenomena of aura colour with perennial existence scientifically. Keywords: Saka, scientific research, experiment method, case study, biofeedback, aura colour